Dopamine agonists upregulate IL-6 and IL-8 production in human keratinocytes - Parrado, Andrea Cecilia (2012)
Aim: Catecholamines regulate functions of the nervous, neuroendocrine and immune systems. Dopamine may modulate the activity of keratinocytes, which play a role in secreting cytokines and chemokines. The aim of this study was to evaluate the effect of dopaminergic agonists on the production of IL-6 and IL-8 by a non-tumoral human keratinocyte cell line (HaCaT). Methods: Cells were stimulated with dopamine and the D2 dopamine receptor agonist cabergoline. Levels of IL-6 and IL-8 in culture supernatants were then determined. Cell proliferation was also assessed. Assays were carried out in the presence or absence of the dopaminergic and β-adrenergic receptor antagonists (sulpiride and propranolol, respectively) and ascorbic acid. Results: Dopamine stimulated the production of IL-6 and IL-8 in a concentration-dependent manner. The effects observed on the secretion of IL-6 were more potent than those corresponding to IL-8 and were reduced by ascorbic acid. The dopamine-induced IL-6 secretion was partially reduced by sulpiride and abrogated by propranolol. The latter drug was able to block the effect of dopamine on the secretion of IL-8. The cabergoline-induced IL-6 release was reduced by sulpiride. Cell viability was not affected by any of the drugs. Conclusions: Dopaminergic agonists can stimulate keratinocytes to produce IL-6 and IL-8 which are related to inflammatory cutaneous processes. These effects are mediated by dopaminergic and β-adrenergic receptors and by receptor-independent oxidative mechanisms.